The analysis of English education students' interest in mathematics courses - Pangadongan, Sri Putri; Purwati, Purwati; Wyrasti, Andi Fajeriani (Journal of Research in Instructional, 2022)
The purpose of this study was to analyze the interest in learning mathematics of twenty English education students at a university in West Papua. This research method is a qualitative research method using descriptive techniques. The procedure of this research starts from the development of the questionnaire instrument, the development of the interview instrument, the validation of the instrument, the distribution of the questionnaire, the determination of the subject, and the interview. Based on the results of data analysis, it is known that the interest in learning mathematics of English education students based on indicators of student interest in learning mathematics is categorized into three groups, namely students who are not interested in learning mathematics, quite interested in learning mathematics, and interested in learning mathematics. Students in the category of the uninterested group have not been able to meet the indicators of interest in learning mathematics. Meanwhile, students in the moderately interested groups can fulfill three indicators of interest in learning mathematics: students' feelings of pleasure in mathematics, students' interest in mathematics, and students' attention to mathematics. Students from the interest group category can fulfill the four indicators of interest in learning mathematics: students' feelings of pleasure in mathematics, student interest in mathematics, student attention to mathematics, and student involvement in mathematics.